Long-term health conditions in UK working-age adults: a cross-sectional analysis of associations with demographic, socioeconomic, psychosocial and health-related factors in an inner-city population. Issue 11 (16th November 2022) - Stagg, Anne L; Hatch, Stephani; Fear, Nicola T; Dorrington, Sarah; Madan, Ira; Stevelink, Sharon A M
Abstract : Objectives: To study the overall disease prevalence, and associations between demographic, socioeconomic, psychosocial, and health-related factors, and self-reporting one or more long-term health conditions (LTCs) in a working-age inner-city population. Design: Cross-sectional household-based survey with a follow-up timepoint. Setting: South-East London Community Health survey data. Participants: 893 adults aged 16–64 years living in Lambeth and Southwark, London. Outcome measures: Prevalence estimates of individual and multiple LTCs. Multinomial logistic regression was used to analyse the association of demographic, socioeconomic, psychosocial and health-related indicators with having one and multiple LTCs at two timepoints. Results: More than one third of participants reported at least one LTC, with the most prevalent being musculoskeletal conditions and asthma. The prevalence of one LTC at both timepoints was 20.6% and 21.4%, and of multimorbidity was 14.0% and 16.4%. At both timepoints, the 35–44 age group showed the largest increase in prevalence of one LTC compared with the preceding age group (16–34). After adjusting for age and gender, small social networks and a larger number of stressful life events were associated with increased risk of having both one and multiple LTCs. The risk of multimorbidity was greater than for initial LTCs for small social networks (3.8 (95% CI: 1.8 to 7.8) compared with 2.0 (95% CI: 1.0 to 3.9)), and three to five stressful life events (3.0 (95% CI: 1.7 to 5.3) compared with 1.5 (95% CI 1.0 to 2.2)). Conclusions: In this study, the prevalence of multimorbidity increased more than the prevalence of one LTC between the two timepoints, indicating a progression of the overall disease prevalence over time. The 35–44 age group showed the greatest increase in the number of initial LTCs which support health-promotion interventions targeting younger age groups. Focusing on increasing social support networks and treating the psychological impact of stressful life events may also be of benefit.